A THREE-DIMENSIONAL NUMERICAL MODEL FOR BAROCLINIC DYNAMIC IN THE MALACCA STRAIT - Taufiq Iskandar et al. (Proceedings of ICMSA, 2005)
The circulation in the Malacca Strait is simulated using a three-dimensionalbaroclinic numerical model. The circulation model isderived from the combined effects of tides, wind, meteorologicalforcings, temperature and salinity. The computational results producedpattern of general circulation and also sea surface temperature andsalinity. In the present study, the pattem of current circulation in theMalacca Strait coincided with the work [7].Keywords: Three-dimensional numerical model; Baroclinic circulation;Sea surface temperature and salinity; Malacca Strait